2010
DOI: 10.1103/physrevb.82.085413
|View full text |Cite
|
Sign up to set email alerts
|

Controlling water dissociation on an ultrathin MgO film by tuning film thickness

Abstract: Periodic density-functional theory calculations at the single-molecule level were used to study dissociation of water on ultrathin MgO films with varying thickness deposited on the Ag͑100͒ surface. The enhanced chemical activity for water dissociation on MgO/Ag͑100͒ originates from the greater stability of dissociated products, which is due in turn to the strong hybridization of their electronic states at the oxide-metal interface. Our results provide insights into the superiority of the monolayer MgO film sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 39 publications
5
60
0
Order By: Relevance
“…Thus, our present finding of thickness-selective surface activity may help to deepen the understanding of the microscopic mechanisms for the chemical reaction of small molecules (such as water) on oxidized Pu surfaces, which is fundamental to the safety issue of nuclear industry. Interestingly, a recent DFT study [47] has reported that the thickness effect of MgO film can be used to control the dissociation of water molecule on surface.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, our present finding of thickness-selective surface activity may help to deepen the understanding of the microscopic mechanisms for the chemical reaction of small molecules (such as water) on oxidized Pu surfaces, which is fundamental to the safety issue of nuclear industry. Interestingly, a recent DFT study [47] has reported that the thickness effect of MgO film can be used to control the dissociation of water molecule on surface.…”
Section: Resultsmentioning
confidence: 99%
“…We believe that these findings give new insights for controlling the interfacial properties of dielectric/metal systems thereby providing the possibility of modulating the work function and the local structure of ultrathin oxide films surfaces which are known to have a significant impact on the reactivity properties of clusters/oxide systems in catalytic applications. 18,54 …”
Section: Discussionmentioning
confidence: 99%
“…In contrast to charge stabilization on bulk insulators, the charge-state-stabilization mechanism on films with nonvanishing tunneling probability depends strongly on the specific properties of adsorbate, film, and substrate [4], and only selected charge states can be stabilized. Despite its important implications for catalysis as well, the transition from films with nonvanishing tunneling probability to bulklike insulating films [8][9][10] in the context of chargestate manipulation is poorly understood.…”
mentioning
confidence: 99%